Effect of CMC Concentration Based on Oil Palm Empty Fruit Bunches and Chitosan Addition on Edible Coating Characteristics on Strawberries - Amelia Rachmawati; Frisnov Andyko; Echa Julia Putri; Ngatirah Ngatirah (G-Tech: Jurnal Teknologi Terapan, 2026)
Strawberries are a fruit that is prone to post-harvest damage because it has a high moisture content and soft tissue structure. Carboxymethyl cellulose-based edible coatings from the fibers of empty bunches of oil palm and chitosan have the potential to maintain the quality of strawberries during storage. This study aims to determine the effect of variations in CMC concentration based on Empty Oil Palm Bunches and chitosan on the edible coating characteristics and the quality of strawberries. The study used a factorial experiment design consisting of CMC concentration (1%, 1.5%, and 2%) and chitosan concentration (1%, 2%, and 3%) with two replications. The observed parameters included viscosity, pH, weight loss, discoloration, and organoleptic properties. The data were analyzed using ANOVA followed by the Duncan test at a significance level of 5%. The results showed that the increase in CMC and chitosan concentrations had a significant effect (p < 0.05) on the increase in viscosity, with values ranging from 6.05–47.01 cP. The pH value ranges from 5.17–5.48 which indicates that the coating solution is relatively stable. The lowest weight loss was obtained in the 2% CMC treatment with an average value of 24.85%. Organoleptic tests showed that color and texture had a real effect, while the scent did not differ noticeably. The best treatment combination was obtained at the concentration of CMC 1.5% and chitosan 2% because it was able to provide the best edible coating characteristics and strawberry quality during storage.